Climate Variability in Indonesia from 615 ka to present: First Insights from Low-Resolution Coupled Model Simulations - Rachmayani, Rima; Prange, Matthias; Schulz, Michael; Ningsih, Nining Sari (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
We analyse the dynamics of Indonesian waters using the results of a set of 13 time-slice experiments simulated by the CCSM3-DGVM model. The experiments were carried out to study global climate variability between and within the Quaternary interglacials of Marine Isotope Stages (MIS) 1, 5, 11, 13, and 15. During boreal summer (June-July-August-September), in most of Indonesia, seasonal surface temperature anomalies can largely be explained by local insolation anomalies induced by the astronomical forcing. However, for some time slices, climate feedbacks may modify the surface temperature response in Indonesia, most pronounced in open water close to the Indian and Pacific Oceans. The warmest boreal summer sea-surface temperature (SST) anomaly compared to Pre-Industrial (PI) conditions of up to 1 K was found in the Banda Sea at 125 ka (MIS 5) and 579 ka (MIS 15). The coolest boreal summer SST anomaly down to –2 K at 495 ka (MIS 13) is equally distributed in Indonesian waters. During boreal winter, most of the moderate cooling over large portions of the land and the waters of Indonesia is also associated with local insolation. The most interesting finding in this study, a dipole and tripole precipitation pattern with up to 3.6 mm/day of rainfall anomaly during boreal summer is identified in the western part of the Indonesian waters, Indian Ocean to Banda Sea, and the eastern part of Indonesian waters. The results of this study are expected to be used as basic information to predict the climate in Indonesia for the present and future. This may add to the assessment provided by the IPCC for a better understanding of future climate change in the region, which is a prerequisite for alleviating its impacts.